Investigations for Ergonomic Presentation of AIS Symbols on ECDIS - Motz, Florian; Widdel, Heino; Oei, Parry; MacKinnon, Scott; Alexander, Lee (The International Hydrographic Review, 2004)
Empirical investigations were carried out in a research project for the German Federal Ministry of Transport, Building, and Housing to evaluate the presentation of AIS target information on ECDIS. The investigations were performed at three international simulation centres. The features, colour and fillingjsize of AIS symbols, as well as the influence of the ECDIS display category on the detection of AIS targets were the main issues of the investigations. Results show that blue (5-52 colour token RE5BL) is the most suitable colour of the tested colours for the presentation of AIS targets under all ambient light conditions on the tested IHO S-52 colour tables.